Impact of chemokines on the properties of spinal cord‐derived neural progenitor cells in a rat spinal cord lesion model. Issue 4 (9th December 2014) - Knerlich‐Lukoschus, Friederike; Krossa, Sebastian; Krause, Jörg; Mehdorn, H. Maximilian; Scheidig, Axel; Held‐Feindt, Janka
Abstract : The existence of endogenous neural progenitor cells (NPCs) in the adult spinal cord (sc) provides the potential for tailored repair therapies after spinal cord injury (SCI). This study investigates the impact of inflammatory mediators on properties of NPC cultures derived from adult rats after SCI. The Infinite Horizon impactor was used to apply 200‐kdyn thoracic sc lesions in adult rats. Control groups received laminectomies to equivalent sc regions. Thoracic sc segments were taken for neurosphere cell cultures. Cell proliferation was found to be significantly higher in lesion groups. Neurosphere‐derived cells differentiated into neurons, oligodendroglia, and astroglia. Lesion cultures exhibited significantly higher amounts of glial fibrillary acidic protein (GFAP) mRNA ( P  < 0.0005) and β‐III‐tubulin mRNA ( P  < 0.05) compared with sham animals. Neurospheres from different treatment groups exhibited the same amounts of tumor necrosis factor‐α, interleukin (IL)−1β, and IL‐6 mRNA. C‐C chemokine receptor (CCR) expression on neurospheres was examined by real‐time RT‐PCR. CCR1 was expressed most consistently in mRNA levels in neurospheres from both treatment groups. After cell differentiation, CCR1 mRNA amounts decreased. CCR1 was detectable by immunohistochemistry in neurospheres and differentiated cells of both groups. Application of CCL3 during differentiation cycles led to significantly higher GFAP mRNA amounts in sham animals compared with CCL3‐free cultures; in contrast, CCL3 had no impact on cell differentiation in the lesion group. In conclusion, impact SCI alters differentiation tendencies and proliferation rates of adult‐derived sc NPCs. Thereby, CCR1/CCL3 promotes specifically astroglial differentiation of NPCs, which provides a potential target for future neurorestorative approaches. © 2014 Wiley Periodicals, Inc.